Effect of a reminder system using an automated short message service on medication adherence following acute coronary syndrome. (1st April 2015) - Khonsari, Sahar; Subramanian, Pathmawathi; Chinna, Karuthan; Latif, Lydia A; Ling, Lee W; Gholami, Omid
Abstract: Background: Medication non-adherence leads to a vast range of negative outcomes in patients with coronary artery disease. An automated web-based system managing short message service (SMS) reminders is a telemedicine approach to optimise adherence among patients who frequently forget to take their medications or miss the timing. Aim: This paper sought to investigate the effect of automated SMS-based reminders on medication adherence in patients after hospital discharge following acute coronary syndrome (ACS). Methods: An interventional study was conducted at a tertiary teaching hospital in Malaysia. A total of 62 patients with ACS were equally randomised to receive either automated SMS reminders before every intake of cardiac medications or only usual care within eight weeks after discharge. The primary outcome was adherence to cardiac medications. Secondary outcomes were the heart functional status, and ACS-related hospital readmission and death rates. Results: There was a higher medication adherence level in the intervention group rather than the usual care group, (χ 2 (2)=18.614, p <0.001). The risk of being low adherent among the control group was 4.09 times greater than the intervention group (relative risk =4.09, 95% confidence interval (CI) 1.82–9.18). A meaningful difference was found in heart functional status between the two study groups with better results among patients who received SMS reminders, (χ 2 (1) = 16.957, p <0.001). Conclusion: An automated SMS-based reminder system can potentially enhance medication adherence in ACS patients during the early post-discharge period.